GAMETHOGENESIS OF PACIFIC SALMONS. 1. DEVELOPMENT OF GONAD IN YOUNG CHUM SALMON ONCORHYNCHUS KETA WALBAUM UNDER VARIOUS TEMPERATURE REGIMES - O. V. Zelennikov (Известия ТИНРО)
Early stages of gametogenesis in young chum salmon are investigated under various temperature regimes at three fish farms of Sakhalin region and in laboratory conditions. In all cases, sex differentiation started after the mass hatching, the age of differentiation varied from 65 to 213 days, but the sum of accumulated degree-days was rather stable — from 620.6 to 669.1. The period from the beginning of sex differentiation to the beginning of previtellogenesis lasted 27–144 days depending on conditions, even for fish in the same fish farm. The lower was the water temperature after the beginning of sex differentiation, the smaller sum of degree-days was accumulated by fish before the beginning of previtellogenic growth of oocytes and the shorter was the period of oocyte growth before the fish release from the farm. The period of previtellogenesis in chum salmon always began before the end of larval period, when weight of the yolk sac was from 1.8 to 18.2 % of the total body weight.